Prevalence and Interventional Outcomes of Patients with Resolution of ST-segment Elevation between Prehospital and In-hospital ECG. (3rd April 2014) - Ownbey, Micah; Suffoletto, Brian; Frisch, Adam; Guyette, Francis X.; Martin-Gill, Christian
Abstract Objective. To determine the prevalence and significance of ST-segment elevation resolution between prehospital and first hospital ECG. Methods. We examined consecutive prehospital ECGs transmitted to a single medical command center in southwestern Pennsylvania between January 1, 2009 and December 31, 2011. We included ECG cases with ST-segment elevation myocardial infarction (STEMI) and excluded cases with incomplete prehospital and/or hospital data. Our primary outcome was ST-segment resolution (STR), defined by cases no longer meeting STEMI criteria on the first in-hospital ECG. Primary variables of interest included prehospital vital signs and treatment, cardiac catheterization findings, and time intervals for diagnostics and treatment. Analysis included t-tests for continuous variables and chi-squared analysis for categorical variables. Results. We reviewed 24, 197 prehospital ECGs and identified 293 cases of prehospital STEMI. Complete hospital and prehospital records were available for 83 cases (28%). Analyzed cohort was an average 62 years old and the majority were male (67%), with a primary complaint of chest pain (93%). STR occurred in 18 cases (22%, CI 14–32%). There were no differences between STR and non-STR cases in prehospital vital signs or treatments. 95% of patients underwent cardiac catheterization with a mean door-to-needle time of 57 minutes (interquartile range 43–71). Comparing STR and non-STR cases, significant lesions (≥50%) were found in 94 and 97% of patients (p = 0.6), and subtotal or total lesions (≥95%) were found in 63 and 85% (p = 0.1), respectively. Conclusions. We found that ST-segment resolution occurred prior to catheterization in 1 of 5 patients with prehospital STEMI, emphasizing the necessity of prehospital ECG in risk stratification of patients with suspected coronary disease. Coronary lesions and intervention rates did not differ between STR and non-STR, suggesting that catheterization is warranted even when STEMI criteria are no longer met in-hospital.